Michelle, Cristina e Dilma: a construção dos ethé femininos nos discursos políticos sul-americanos? - Mesti, Paula Camila (Universidade Federal de São Carlos, 2017)
The transformations that took place in the history of women, the changes in political discourse, the new methodologies used in Discourse Analysis formed the backdrop for this research that focuses on the way of construction and incorporation of ethé by presidents Michelle Bachelet (Socialist Party - Chile), Cristina Fernández de Kirchner (Justicialista Party - Argentina) and Dilma Rousseff (Trabalhadores Party - Brazil). Using as corpus of analysis the videos of the television interviews made with these South American presidents, this work aimed to demonstrate interpretive gestures that showed how the images of the presidents were constructed in the statements of the questions asked by the journalists, in the statements of the answers given by these political subjects and also in the comments posted by Internet users. For that, discursive sequences were selected and analyzed in which it was verified which types of ethé were constructed by these three different instances. The analyzes of the television interviews, consisting of questions addressed to the presidents, full of stereotypes, personal questions and uninteresting questions (from the historical and economic point of view), opened the way for the considerations about the discursive ethos and the reconstruction of the image of the self in and by disours. These same personal questions made it possible to reflect on the reflected ethos, observed both in the questions proposed by journalists and in the comments posted by Internet users on YouTube videos. Finally, it should be said that with the deepening of the analyzes it was found that the current studies on the notions of reflected ethos, fixed ethos, female ethos and reconstruction of the ethos are quite productive. In this way, it is believed that this work has contributed, even if minimally, to the beginning of the dissemination and circulation of new theoretical and methodological trends on the discursive ethos in Brazil.
Michelle, Cristina e Dilma: the construction of the feminine ethé in the political discours of south american?
Keywords: Ethos discursivo; Ethos refletido; Ethos fixado; Deslocamento teórico-metodológico; Discursive ethos; Reflected ethos; Fixed ethos; Theoretical-methodological shift; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA